Anatomical characterization of the brachial plexus in dog cadavers and comparison of three blind techniques for blockade. (March 2018) - Skelding, Alicia; Valverde, Alexander; Sinclair, Melissa; Thomason, Jeffrey; Moens, Noel
Abstract: Objectives: To describe the ventral spinal nerve rami contribution to the formation of the brachial plexus (BP), and to compare ease of performing and nerve staining between three blind techniques for BP blockade in dogs. Study design: Prospective, randomized, blind study. Animals: A total of 18 dog cadavers weighing 28.2 ± 9.7 kg (mean ± standard deviation). Methods: Dogs were randomly assigned to two of three BP treatments: traditional approach (TA), perpendicular approach (PA), and axillary approach (AA). Dye (0.2 mL kg −1 ) was injected in the left BP using a spinal needle; another BP treatment was used in the right BP. Landmarks (L) included: L1, midpoint between point of the shoulder and sixth cervical (C6 ) transverse process; L2, scapulohumeral joint; and L3, first rib. For TA, the needle was introduced craniocaudally through L1, medial to the limb and cranial to L3. For PA, the needle was directed perpendicular and caudal to L2, aligned with L1, until cranial to L3. For AA, the needle was directed ventrodorsally, parallel and cranial to L3 until at L1. All BPs were scored for dyeing quality [0 (poor) to 5 (excellent)]. The left BP was dissected for nerve origins. Durbin test was used to compare scores ( p < 0.05). Results: In all dogs, the musculocutaneous nerve originated from C7 and C8 ; the radial nerve from C8, the first thoracic vertebra (T1 ) (16/18 dogs) and C7 (2/18); and the median and ulnar nerves from C8, T1 (17/18) and C7 (1/18). Respective raw scores and adjusted scores for the incomplete block design were not significantly different ( p  = 0.72; ranks TA 16.5, PA 19.0, AA 18.5). Conclusions and clinical relevance: The musculocutaneous, median, ulnar and radial nerves originate from C7, C8 and T1 . Regardless of the technique, knowledge of anatomy and precise landmarks are relevant for correct dye dispersion.